Similarities And Differences Of Euphemisms Related To Negative Human Behavior In The English And Uzbek Languages (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are some language units and combinations that make it difficult to compare the original text. To solve these difficulties and problems of comparison, there must be special principles, rules and criteria. Moreover, the study of these problems requires the use of various transformations and principles in the transition from one language to another. Comparison matches found in one language cannot be found in another language, if they occur in the area of ​​the work, they cannot be found in another. This article studies the euphemisms related to the negative behavior in the English and Uzbek languages with the aim of identifying the similarities and differences between these two languages. This study also attempts to explore the most common euphemistic terms used in English and Uzbek. While they have some common features, they differ in their use of some euphemistic strategies.